National Program For The Training Of Basic Education Teachers: A Study on its contributions to the adequacy of teacher training - Bethônico, Mariana (2024)
This article presents the results of a master’s thesis, which sought to analyze PARFOR regarding the fulfillment of the objectives it proclaimed as a public policy. Thus, considering that the program seeks to promote the adequacy of teacher training to their respective areas of activity in basic education, it was considered relevant to verify to what extent this training/performance conformation has actually occurred. Data analysis indicated that the program partially meets its objective, but also represents a great opportunity for the qualification of teachers in the public network, especially in poorer locations with greater difficulty in accessing higher education.